β-Asarone Inhibits Amyloid-β by Promoting Autophagy in a Cell Model of Alzheimer's Disease - Wang, Nanbu; Wang, Haoyu; Li, Lingyu; Li, Yunchuan; Zhang, Ronghua (Frontiers in Pharmacology, 2020)
Alzheimer's disease (AD) is one of the most common types of dementia that causes memory, thinking and behavior problems. The most important feature of AD is the gradual irreversible loss of cognitive ability through the formation of amyloid β (Aβ) plaques and neurofibrillary tangles composed of tau protein. The metabolism of Aβ and tau proteins is closely related to and is affected by autophagy. Current research speculates that autophagy dysfunction leads to an increase in harmful proteins in AD. β-asarone is the main constituent of Acorus tatarinowii Schott and has important effects on the central nervous system. In this paper, we primarily explored the effects of β-asarone on the clearance of noxious proteins and the associated potential mechanisms via autophagy in a PC12 cell model. A CCK-8 assay and LDH experiments were used to assess cell viability/toxicity, and SPiDER-βGal was used to detect cellular senescence. The important proteins associated with the pathogenesis of AD including APP, PS1, Aβ, BACE1 and SYN1 were analyzed by immunofluorescence (IF) and Western blot analysis. Antimycin A (A3) and cyclosporine A (CSA) were selected as the activators and inhibitors of autophagy, respectively. LC3, BECN, P62, PINK1 and Parkin protein expression was also examined by IF and Western blot analysis. The data showed that β-asarone administration significantly dose-dependently increased cell proliferation and decreased cytotoxicity; moreover, β-asarone inhibited SA-β-Gal and improved cell senescence. The results further showed that, compared to the model, APP, PS1, Aβ, BACE1 and p62 were reduced, while SYN1, BECN1 and LC3 were increased after treatment with β-asarone. The results of Canonical Correlation Analysis (CCA) showed a highly significant relationship between the pathological factors of AD and the protein expression of autophagy. In conclusion, our study demonstrated that β-asarone can inhibit Aβ, and this effect may occur by promoting autophagy in a cell model of AD.